Persistence of Ebola virus in semen among Ebola virus disease survivors in Sierra Leone: A cohort study of frequency, duration, and risk factors. - A E Thorson; G F Deen; K T Bernstein; W J Liu; F Yamba; N Habib; F R Sesay; P Gaillard; T A Massaquoi; S L R McDonald; Y Zhang; K N Durski; et al. (PLoS Medicine)
Background Sexual transmission chains of Ebola virus (EBOV) have been verified and linked to EBOV RNA persistence in semen, post-recovery. The rate of semen persistence over time, including the average duration of persistence among Ebola virus disease (EVD) survivors, is not well known. This cohort study aimed to analyze population estimates of EBOV RNA persistence rates in semen over time, and associated risk factors in a population of survivors from Sierra Leone. Methods and findings In this cohort study from May 2015 to April 2017 in Sierra Leone, recruitment was conducted in 2 phases; the first enrolled 100 male participants from the Western Area District in the capital of Freetown, and the second enrolled 120 men from the Western Area District and from Lungi, Port Loko District. Mean age of participants was 31 years. The men provided semen for testing, analyzed by quantitative reverse transcription PCR (qRT-PCR) for the presence of EBOV RNA. Follow-up occurred every 2 weeks until the endpoint, defined as 2 consecutive negative qRT-PCR results of semen specimen testing for EBOV RNA. Participants were matched with the Sierra Leone EVD case database to retrieve cycle threshold (Ct) values from the qRT-PCR analysis done in blood during acute disease. A purposive sampling strategy was used, and the included sample composition was compared to the national EVD survivor database to understand deviations from the general male survivor population. At 180 days (6 months) after Ebola treatment unit (ETU) discharge, the EBOV RNA semen positive rate was 75.4% (95% CI 66.9%-82.0%). The median persistence duration was 204 days, with 50% of men having cleared their semen of EBOV RNA after this time. At 270 days, persistence was 26.8% (95% CI 20.0%-34.2%), and at 360 days, 6.0% (95% CI 3.1%-10.2%). Longer persistence was significantly associated with severe acute disease, with probability of persistence in this population at 1 year at 10.1% (95% CI 4.6%-19.8%) compared to the probability approaching 0% for those with mild acute disease. Age showed a dose-response pattern, where the youngest men (≤25 years) were 3.17 (95% CI 1.60, 6.29) times more likely to be EBOV RNA negative in semen, and men aged 26-35 years were 1.85 (95% CI 1.04, 3.28) times more likely to be negative, than men aged >35 years. Among participants with both severe acute EVD and a higher age (>35 years), persistence remained above 20% (95% CI 6.0%-50.6%) at 1 year. Uptake of safe sex recommendations 3 months after ETU discharge was low among a third of survivors. The sample was largely representative of male survivors in Sierra Leone. A limitation of this study is the lack of knowledge about infectiousness. Conclusions In this study we observed that EBOV RNA persistence in semen was a frequent phenomenon, with high population rates over time. This finding will inform forthcoming updated recommendations on risk reduction strategies relating to sexual transmission of EBOV. Our findings support implementation of a semen testing program as part of epidemic preparedness and response. Further, the results will enable planning of the magnitude of testing and targeted counseling needs over time.